Validating an adjustment to the intermittent critical power model for elite cyclists—modeling w' balance During world cup team pursuit performances - Bartram, J. C.; Thewlis, D.; Martin, D. T.; Norton, K. I. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Modeling intermittent work capacity is an exciting development to the critical power model with many possible applications across elite sport. With the Skiba 2 model validated using subelite participants, an adjustment to the model`s recovery rate has been proposed for use in elite cyclists (Bartram adjustment). The team pursuit provides an intermittent supramaximal event with which to validate the modeling of W' in this population.